Colonization of unfamiliar landscapes : the archaeology of adaptation - Rockman, Marcy, 1971-; Steele, James, 1960- (Routledge, 2003)
The process of familiarization with and adaptation to unfamiliar landscapes has been integral to colonization and settlement throughout human history. This innovative and important volume presents the archaeological and anthropological foundations of the landscape learning process. Contributions apply the related fields of ethnography, cognitive psychology, and historical archaeology to the issues of individual exploration, development of trail systems, folk knowledge, social identity, and the role of the frontier in the growth of the modern world. A series of case studies examines the archaeo.